L-Carnitine and Acetyl-L-Carnitine: Potential Novel Biomarkers for Major Depressive Disorder - Nie, Li-Juan; Liang, Jun; Shan, Feng; Wang, Bao-Shi; Mu, Yuan-Yuan; Zhou, Xie-Hai; Xia, Qing-Rong (Frontiers in Psychiatry, 2021)
The lack of biomarkers greatly limits the diagnosis and treatment of major depressive disorder (MDD). Endogenous L-carnitine (LC) and its derivative acetyl-L-carnitine (ALC) play antidepressant roles by improving brain energy metabolism, regulating neurotransmitters and neural plasticity. The levels of ALC in people and rodents with depression are significantly reduced. It is necessary to determine whether serum LC and ALC might be used as novel biomarkers for the diagnosis of MDD. Here, ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to determine the concentration of LC and ALC in the serum of healthy controls and patients with MDD; among the latter, in patients who were responsive (effective group) and non-responsive (ineffective group) after 2 weeks of treatment. The diagnostic value of serum LC and ALC for MDD was assessed. Compared with healthy controls, the serum LC and ALC concentrations in patients with MDD were significantly decreased (P < 0.001). Pearson correlation analysis shows that the HDRS-24 score was negatively associated with serum ALC (r = −0.325, P = 0.007). Receiver operating characteristic (ROC) analysis revealed an area under the curve (AUC) of 0.801 with 83.1% sensitivity and 66.3% specificity for LC, and an AUC of 0.898 with 88.8% sensitivity and 76.4% specificity for ALC, differentiating patients with MDD from healthy controls. Furthermore, the concentration of LC and ALC in patients with depression was significantly increased in the effective treatment group, and no significant change was observed in the ineffective treatment group. These results suggest that serum LC and ALC may be novel biomarkers for the diagnosis of MDD.